1987
DOI: 10.1038/bjc.1986.213
|View full text |Cite
|
Sign up to set email alerts
|

Drug sensitivity of non small cell carcinoma of lung by clonogenic assay in several media

Abstract: Summary Lung tumours of non small cell pathology were cultured by clonogenic assay in several media. Culture was successful in spleen conditioned medium, but only 57% grew and low plating efficiencies (PE) meant that only 23% of the original number produced significant drug results. Comparison of rat erythrocyte lysate (REL) medium with serum free defined medium (HITES) and HITES +10% FBS demonstrated clear enhancement of PE in REL although growth was 100% successful in all these media. Ninety-three percent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We were interested in its potential use for the enhancement of cytotoxicity of vindesine and cisplatinum in non-small cell cancer of lung (NSCCL). An earlier study (Simmonds et al, 1986) using primary patient material in clonogenic assay has confirmed the overall poor clinical response rates to these drugs reported by Elliott et al (1984).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…We were interested in its potential use for the enhancement of cytotoxicity of vindesine and cisplatinum in non-small cell cancer of lung (NSCCL). An earlier study (Simmonds et al, 1986) using primary patient material in clonogenic assay has confirmed the overall poor clinical response rates to these drugs reported by Elliott et al (1984).…”
mentioning
confidence: 51%
“…We were interested in its potential use for the enhancement of cytotoxicity of vindesine and cisplatinum in non-small cell cancer of lung (NSCCL). An earlier study (Simmonds et al, 1986) using primary patient material in clonogenic assay has confirmed the overall poor clinical response rates to these drugs reported by Elliott et al (1984).In this study, 18 lung tumour samples, 17 squamous and 1 adenocarcinoma, were removed at thoracotomy of previously untreated patients and grown in the bilayered agar clonogenic assay system. In brief, samples were mechanically disaggregated with crossed scalpels in Hanks balanced salt solution (HBSS) with penicillin and streptomycin and resulting cell suspensions passed through needles of decreasing gauge to obtain single cells.…”
mentioning
confidence: 73%